Risks of infectious diseases in the subjective perception of metropolitan residents: From assessment to management strategy - N. A. Lebedeva-Nesevria; S. Yu. Sharypova; M. D. Kornilitsyna (Кубанский научный медицинский вестник, 2024)
Background. In the post-pandemic period, Russia is characterized by a relatively high level of infectious morbidity, combined with the “infection surveillance” of the population and fear of possible epidemics. Managing health risks associated with the spread of infections requires a comprehensive approach that addresses both the healthcare system and individual behavior. Objective. To identify the features of subjective risk perception regarding infectious diseases and to describe behavior risk-associated strategies in a sample of urban populations in the Russian Federation. Methods. An empirical study was conducted using a mixed methodology. The first phase involved a formalized survey (n = 300) aimed at measuring the subjective perception of infectious disease risk and related behaviors. The second phase included an analysis of in-depth interviews (n = 11) in order to clarify the essence of behavior strategies aimed at managing the infectious disease risk. Descriptive statistics, odds ratio calculations, as well as correlation and factor analyses were employed for processing quantitative data by means of SPSS Statistics 21.0. Qualitative data analysis involved open and axial coding. Results. The development of infectious diseases is perceived as the most significant risk among residents of Russian metropolitan areas. The majority of respondents (80%) rate the risk at 0.5 or higher (indicating alarming and high levels of risk) and implement various measures for its management. Determinants influencing strategy choice include age (Pearson’s r = (-)0.539 at p < 0.001) and parental status (Spearman’s ρ = 0.360 at p < 0.05). Subjective risk assessment is not considered a statistically significant predictor of individual activity regarding risk. Factor analysis (model explanatory capacity 53%, p < 0.001) identified groups of actions aimed at risk reduction: 1) information seeking, 2) creating a protective space, and 3) interacting with the external environment. In-depth interview analysis clarified that despite a documented inclination towards action, individual behavior can be characterized as passive adaptation to the risk. Conclusion. Risk perception is found to be not a primary or necessary factor in choosing an active risk management strategy. The reluctance to take risk-reducing actions is associated with an external locus of control, which involves a belief that risk is uncontrollable and assigning responsibility to other subjects of the risk space. The findings may be considered in the development and improvement of measures to prevent the spread of infectious diseases, including health risk communication strategies